THE IMPACT OF USER-GENERATED CONTENT ON CONSUMER CERTAINTY IN HIGHER EDUCATION INSTITUTIONS CHOICES - Angelique Tiffany Tarigan Tua, Michelle
With the increasing availability of the internet and mobile devices, User-Generated Content (UGC) is now more prevalent than ever on social media platforms. The growth of home devices, sources, and applications that enable at-home production, the ability to create and distribute content has increased rapidly. User-Generated Content has been utilized by marketers as a digital form of word-of-mouth marketing in various industries. This study investigates the impact of User-Generated Content (UGC) of Consumer Certainty (CC) of prospective students while aiming to understand the dynamics when interacting with Marketer-Generated Content (MGC) and Quality Assurance (QA) as moderating factors. Research on User-Generated Content impact in higher education still lacks, hence this study attempts to fill that gap. Through a Google Forms questionnaire of 104 high school students or prospective students looking for higher education in Indonesia, respondents are asked to fill a four part, 5-point Likert Scale questions to quantify the impact of UGC, QA, and MGC toward CC. Using a quantitative method with moderated regression analysis on SPSS, the results show no significance of User-Generated Content on Consumer Certainty when interacting independently but shows different effects when interacting with its moderating factors, QA and MGC. This study contributes knowledge regarding the role of User-Generated Content in consumer’s decision making process of higher education institutions choices. In addition, this study provides marketers insights on utilizing User-Generated Content alongside their Marketer-Generated Content and Quality Assurance.